The Importance of Marketing in Agricultural Enterprises - Abitjanovna, Khodjaeva Shodiyabonu (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses the main functions of enterprise marketing and the possibility of creating competitive products for business, issues of modernizing enterprise management and marketing know-how, as well as ownership of marketing elements.